A motivational theory perspective on entrepreneurial intentions: a gender comparative study. Issue 2 (8th September 2020) - Arshad, Muhammad; Farooq, Mariam; Atif, Muhammad; Farooq, Omer
Abstract : Purpose: This study aims to analyze individuals' entrepreneurial intentions from the perspective of motivational theory and examines the effects of intrinsic and extrinsic factors on entrepreneurial intentions of male and female individuals. Design/methodology/approach: Data were collected from students graduating from Pakistan's largest university. A structural equation modeling technique was used for model testing. Findings: Intrinsic factors such as intrinsic interest and community feeling aspiration and extrinsic factors such as perceived relative income and occupational prestige positively affect attitudes and, in turn, stimulate entrepreneurial intentions. Further, as intrinsic interest and perceived relative income scored higher among men, gender moderates those effects. Conversely, the entrepreneurial attitudes of women were primarily driven by community feeling aspiration. Notably, the positive effect of occupational prestige did not vary among men and women. Originality/value: This paper explores the roles of intrinsic and extrinsic factors in the entrepreneurial intentions of men and women. The integration of motivational theory with gender provides insights into the determinants of entrepreneurial intentions in South Asia.